Culture-independent approaches to chlamydial genomics - Taylor-Brown, Alyce (Microb Genom, 2018)
The expanding field of bacterial genomics has revolutionized our understanding of microbial diversity, biology and phylogeny. For most species, DNA extracted from culture material is used as the template for genome sequencing; however, the majority of microbes are actually uncultivable, and others, such as obligate intracellular bacteria, require laborious tissue culture to yield sufficient genomic material for sequencing. Chlamydiae are one such group of obligate intracellular microbes whose characterization has been hampered by this requirement. To circumvent these challenges, researchers have developed culture-independent sample preparation methods that can be applied to the sample directly or to genomic material extracted from the sample. These methods, which encompass both targeted [immunomagnetic separation-multiple displacement amplification (IMS-MDA) and sequence capture] and non-targeted approaches (host methylated DNA depletion-microbial DNA enrichment and cell-sorting-MDA), have been applied to a range of clinical and environmental samples to generate whole genomes of novel chlamydial species and strains. This review aims to provide an overview of the application, advantages and limitations of these targeted and non-targeted approaches in the chlamydial context. The methods discussed also have broad application to other obligate intracellular bacteria or clinical and environmental samples.